2005
DOI: 10.4102/ojvr.v72i1.225
|View full text |Cite
|
Sign up to set email alerts
|

The performance of Orma Boran and Maasai Zebu crossbreeds in a trypanosomosis endemic area of Nguruman, south western Kenya

Abstract: <span style="font-family: arial,helvetica;">Studies on the trypanotolerance of Orma Boran X Maasai Zebu (Orma Zebu) crossbred cattle (F1 progeny) and pure-bred Maasai Zebu contemporaries were carried out in Nguruman, south western Kenya. The two groups were monitored from birth for a period of 2 years. The incidence of trypanosomosis, parasitaemia, packed cell volume (PCV), body mass and average daily mass gain were monitored. During the study period, overall trypanosomosis incidence was low (3 %). The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The trypanotolerant trait is generally attributed to the taurine breeds of cattle in West and Central Africa, namely, the N’Dama and the West African shorthorn (WASH) ( Hoste et al , 1992; Maganga et al , 2017; Mattioli et al , 1998; Mattioli et al , 1999; Roelants, 1986; Trail et al , 1990; Trail et al , 1994). Similar observations have been made for the Orma Boran X Maasai Zebu (Orma Zebu) crossbred cattle in East Africa ( Maichomo et al , 2005; Mwangi et al , 1998a; Mwangi et al , 1998b). Studies have shown that the basis of this trait was associated with the capacity of these animals to develop less severe anaemia in the face of infection ( Berthier et al , 2015; Mattioli et al , 1998; Murray et al , 1982; Murray & Dexter, 1988; Trail et al , 1990).…”
Section: Introductionsupporting
confidence: 79%
“…The trypanotolerant trait is generally attributed to the taurine breeds of cattle in West and Central Africa, namely, the N’Dama and the West African shorthorn (WASH) ( Hoste et al , 1992; Maganga et al , 2017; Mattioli et al , 1998; Mattioli et al , 1999; Roelants, 1986; Trail et al , 1990; Trail et al , 1994). Similar observations have been made for the Orma Boran X Maasai Zebu (Orma Zebu) crossbred cattle in East Africa ( Maichomo et al , 2005; Mwangi et al , 1998a; Mwangi et al , 1998b). Studies have shown that the basis of this trait was associated with the capacity of these animals to develop less severe anaemia in the face of infection ( Berthier et al , 2015; Mattioli et al , 1998; Murray et al , 1982; Murray & Dexter, 1988; Trail et al , 1990).…”
Section: Introductionsupporting
confidence: 79%
“…4 A better understanding of trypanotolerance, the ability of some indigenous breeds of cattle and other ruminants to resist sickness despite latent infection, seems to be the most promising approach to disease control. [5][6][7] A mouse model of genetic control of trypanotolerance exists based on A/J as a susceptible strain and C57BL/6 as a tolerant strain. This model is widely accepted and has led to the identification of five major quantitative trait loci (QTL) on mouse chromosomes 1, 5 and 17, associated with survival time.…”
Section: Introductionmentioning
confidence: 99%
“…A few sources provided information relating to all production systems [32,41], others for the pastoralist systems [42][43][44], for the agro-pastoral and mixed farming systems [29,31,[45][46][47][48][49][50] and for the high milk yield "grade" dairy cattle kept in a separate system alongside indigenous cattle in the agro-pastoral and mixed farming systems [51][52][53]. Table 4.…”
Section: Parameterising the Cattle Production Systemsmentioning
confidence: 99%